Mobile Health Interface Analysis: Usability Assessment of the Sembada Application for Non-Communicable Disease Monitoring - Dian Wijayanti; Weni Kurdanti; Tri Siswati (Knowledge Dynamics, 2025)
Background: Early detection of non-communicable diseases (NCDs) through integrated guidance posts (Posbindu PTM) can be enhanced through mobile health applications. This study aimed to develop and evaluate the usability of Sembada m-Health, an Android-based application for conducting Posbindu PTM activities at Sleman Regional General Hospital. Methods: This Research and Development study employed the Four D model (Define, Design, Develop, Disseminate). The define phase involved stakeholder needs assessment through Focus Group Discussions. The design phase encompassed application development by IT experts, while the develop phase included multi-level testing by material experts (n=2), media experts (n=2), and end-users (n=30). Structured questionnaires assessed media and material aspects, while the Post-Study System Usability Questionnaire (PSSUQ) evaluated user experience. The disseminate phase included application socialization and qualitative evaluation. The study was conducted in Yogyakarta from October 2021 to April 2022, with feasibility thresholds set at ≥4.20 for media and material aspects and ≤2.82 for PSSUQ. Results: The application exceeded all feasibility thresholds, scoring 4.62 for media aspects, 4.23 for material aspects, and 1.71 on the PSSUQ. Stakeholders expressed high satisfaction with Sembada m-Health's system functionality, particularly its support for individual health monitoring, program implementation, NCD risk factor tracking, and personalized recommendations. Conclusions: Sembada m-Health demonstrated high usability and feasibility for supporting the Posbindu PTM program. Future research should focus on evaluating its long-term impact on NCD prevention and management outcomes.